Markov Chains Slash Inventory Costs in Indonesia: Rantai Markov Memangkas Biaya Persediaan di Indonesia - Mishani, Adinda Chamilia; Sukmono, Tedjo (Indonesian Journal of Innovation Studies, 2024)
PT. Varia Usaha Beton, facing an 8% decline in 2022 targets due to uncontrolled inventory and a 15,150-ton overstock of sand at its BSP Sayung plant, needed an effective solution. This study applied a Markov chain model with perfect enumeration to optimize sand inventory management. Qualitative data from observations, expert interviews, and company records (2021-2022) and quantitative analysis identified Policy 58 as optimal, reducing excess costs to Rp. 32,463,360 monthly. Implementing improvements in specific overstock states (3, 4, 5, and 6) provides a strategic approach to minimize sand overstock and associated costs. Highlight: Inventory Decline: 8% target drop due to uncontrolled inventory in 2022. Optimal Policy: Policy 58 reduced monthly excess costs to Rp. 32,463,360. Strategic Improvements: Implement changes in states 3, 4, 5, and 6 to manage overstock. Keywoard: Inventory Control, Markov Chain, Perfect Enumeration, Overstock Management, Construction Materials